ENHANCING STUDENTS’ SPEAKING ABILITY AT 10TH GRADE OF COMPUTER AND NETWORK ENGINEERING CLASS AT SMKN 4 MALANG THROUGH L1/L2 BASED STRATEGIES - Rizki Junaida; Santi Prastiyowati (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2018)
The lack of speaking practice will cause some communication problems. When language learners do not know how to say a word in English, they can communicate effectively by using their hands, imitating sounds, using new words, or describing what they mean. Those ways can be done by the studentsas communication strategies. This research is aimed to describe the enhancement of students’ speaking ability at Computer and Network Engineering Class C of SMKN 4 Malang by using L1/ L2 based strategies. This Class Action Research (CAR) was conducted at SMKN 4 Malang. The subjects of this research were the students of thenth-grade of Computer and Network Engineering  Class C, which consisted of 33 students. This classroom action research was conducted through the following procedures: preliminary observation, planning, implementing, observation, and reflection. There were two major indicators used as the criteria of success in this research. First, mean score of the post test was ≥ 75. Second, there should be 50% of students get score ≥ 75. Before conducting this research, a preliminary study was conducted to know the students’ problem in speaking skill. The result of the speaking test in preliminary study showed that the mean score of 33 students was 64.8. There were only 7 students who got score ≥ 75. In Cycle I, L1/L2 based strategy showed the improvement of students’ speaking. The mean score of Cycle I was 67.5. The Cycle 1 failed because the students who got ≥ 75 were only 6 students which were consisting of 21%. However, the mean score of Cycle II was 78.6. It means that the first criterion of success was achieved. Moreover, the students who got score ≥75 were 75.9%. Therefore, the all criteria of success were achieved. To sum up, the result of classroom action research proved that L1/L2 based strategies could enhance speaking ability at 10th Grade of Computer and Network Engineering Class C at SMKN 4 Malang.